2022
DOI: 10.1007/s00380-022-02204-x
|View full text |Cite|
|
Sign up to set email alerts
|

Subcutaneous versus transvenous implantable cardioverter-defibrillator among drug-induced type-1 ECG pattern Brugada syndrome: a propensity score matching analysis from IBRYD study

Abstract: No real-world data are available about the complications rate in drug-induced type 1 Brugada Syndrome (BrS) patients with an implantable cardioverter-defibrillator (ICD). Aim of our study is to compare the device-related complications, infections, and inappropriate therapies among drug-induced type 1 BrS patients with transvenous- ICD (TV-ICD) versus subcutaneous-ICD (S-ICD). Data for this study were sourced from the IBRYD (Italian BRugada sYnDrome) registry which includes 619 drug-induced type-1 BrS patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A recent study involving 258 patients has revealed no significant differences in inappropriate ICD therapies, device-related complications, or infections between the population of drug-induced type-1 BrS patients with subcutaneous-ICD and those with transvenous-ICD. Furthermore, there's evidence suggesting that the use of subcutaneous-ICD may potentially reduce the risk of complications related to lead in patients with ICDs ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study involving 258 patients has revealed no significant differences in inappropriate ICD therapies, device-related complications, or infections between the population of drug-induced type-1 BrS patients with subcutaneous-ICD and those with transvenous-ICD. Furthermore, there's evidence suggesting that the use of subcutaneous-ICD may potentially reduce the risk of complications related to lead in patients with ICDs ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the increasing use of subcutaneous ICDs (S-ICD) raises questions about the efficacy of such devices in cardiomyopathies and how to evaluate clinical arrhythmic endpoints. Although no clinical trial was conducted specifically in the setting of cardiomyopathies, substantial evidence suggests that S-ICD efficacy appears non-inferior to transvenous ICDs in terms of preventing SCD and all-cause mortality [42,43]. Moreover, the inability of S-ICD to perform ATP was PLOS ONE not associated with a higher risk of MAE.…”
Section: Limitationsmentioning
confidence: 99%
“… 5 Moreover, a recent study has shown no significant differences in inappropriate ICD therapies, device-related complications, and infections between S-ICD and TV-ICD among BrS patients. 6 …”
mentioning
confidence: 99%